248 Epidemiology of injuries in scottish male professional rugby union. (3rd March 2020) - Bailey, Stuart; Martindale, Russell; Robson, James; Palmer, Debbie
Abstract : Background: The rate of injury in men's professional rugby union tends to be greater than other team/field based sports. Epidemiological studies are required to demonstrate the magnitude of the injury situation and to inform future injury prevention measures. Objective: To analyse injuries sustained by male professional rugby union players in Scotland. Design: Prospective observational study. Setting: Match and training time-loss injuries sustained by players in their professional club (Edinburgh Rugby and Glasgow Warriors) and Scotland International Men's team during the 2017/18 season were recorded by Scotland Rugby medical staff. Exposure (hours) during training or match play was recorded by GPS device (on-pitch) or player-RPE (off-pitch). Patients (or Participants): 229 players (24.7±4.1 years) were involved in the study (professional club n=149; Scotland international n=80). Sixty-two players were present in both cohorts. Interventions (or assessment of risk factors): Match and training injuries and level of play (professional club vs. international) were compared. Main outcome measurements: Injury incidence, severity, type and location. Results: Match injury incidence was 128.7/1000 player match hours (severity: 19.4±30.7 days) and 118.2/1000 player match hours (severity: 43.3±50.4 days) for professional club and international rugby, respectively. Training injury incidence was 4.7/1000 player hours (severity: 29.1±56.2 days) and 4.6/1000 player hours (severity: 24.2±35.6 days) for professional club and international rugby, respectively. Concussion (professional club: 32.0/1000 player match hours; international: 31.8/1000 player match hours) and lower limb muscle/tendon injuries (professional club: 1.9/1000 player hours; international: 1.9/1000 player hours) were the most frequent match and training injuries respectively. Conclusions: Match injury incidence is higher than training injury incidence in professional Scottish rugby union, with concussion and lower limb muscle/tendon injuries the most common match and training injury diagnoses, respectively. These findings are in agreement with previous studies.